Naturalizowanie epistemologii - Hetmański, Marek (Filozofia Nauki, 2008)
Classic epistemology is under manifold changes; its categories loose their traditional meanings and gain new ones. Civilization and cultural changes, especially in mass communication and scientific knowledge, make impossible to insist on the concept of knowledge entirely as a true and justified belief. Traditional concepts of individual and subjectivistically conceived agent as well as concept of objects (areas and domains) of human knowledge are to much restrictive and at the same time controversial. Epistemological (pure philosophical) meaning of them is constantly confronted and changed by the scientific discoveries and definitions, coming especially from natural and social sciences (biology, neural sciences, psychology and social sciences). It is long-lasting and manifold process of naturalization that regards not only cognitive phenomena but epistemic categories and epistemological theories as well. The papers presents the concise model of the naturalized theory of human knowledge one can eliminate from different positions and theories. Today types of naturalized epistemology try to go beyond the strict and limited concept of naturalism (Quine’s naturalized epistemology) and go toward anti-scientific, more liberal understanding of it. Naturalizing epistemology opens, as it is argued in the paper, the new perspectives and prospects on human cognition and knowledge that are far from the classic concepts.